The Impact of the Faculty of Medicine, University of Gezira, Innovative Programme on its Graduates - Osman, Wail N; Abubakr, Diaa-eldin E; M, Mohammed Elsanousi (Gezira Journal of Health Sciences, 2013)
Introduction : Programme evaluation is the collection and interpretation, through systemic and formal means, of relevant information which serves as a basis for rational judgment in decision situations. This study was conducted as part of the third programme development of the Faculty of Medicine, Gezira University 2010 – 2011. Objectives : The general objective is to study the impact of the Faculty of Medicine, Gezira University, innovative programme, on its graduates. The specific objectives include the evaluation of graduates' competences in the three main areas of domain of learning, i.e. Knowledge, skills and attitude. Materials and Methods : This is a Cross-sectional Study conducted in the period from13 th. of January to 12 th. of February 2011. The study population includes 146 consultants who have Gezira graduates training with them including house officers, medical officers and registrars. Excluded from the study all consultants who are academic staff members in the FMUG, who are Gezira graduates or who are involved in student training. A questionnaire was designed to answer the questions that address the objectives of the study covered in 32 questions, using a grading scales; 1 to 5: where 1= poor; 2= less than average, 3= average; 4= good; 5= excellent. Results: the response rate for the questionnaire was 73% (146/210), representing 146 consultants working in 23 hospitals in 12 cities. In the overall evaluation of graduates΄ knowledge and cognitive abilities, graduates were rated as good to excellent in (68.3%), average in (25.12%) and poor to below average in only a minority of the graduates. In the overall evaluation of graduates΄ skills and competences, graduates were rated as good to excellent in (72.33%), average in (20.81%) and poor to below average in only a minority of the graduates. In the overall evaluation of attitudes and ethical standards, graduates were rated as good to excellent in the majority (84.06%). In the overall classification, graduates were rated as good to excellent in the vast majority (82.6%), average in the minority (14.5%) and poor to below average in only a few cases. Conclusion The evaluation of graduates' competences is an important element in the educational programme evaluation. These results provide evidence in favour for the innovative educational programme and can encourage other medical schools to adopt it. Further studies are needed to cover other aspects of graduates' evaluations.